2020
DOI: 10.3390/ijms21082752
|View full text |Cite
|
Sign up to set email alerts
|

Mark4 Inhibited the Browning of White Adipose Tissue by Promoting Adipocytes Autophagy in Mice

Abstract: Autophagy can remove excess or dysfunctional proteins and organelles to maintain cellular homeostasis. Browning of white adipose tissue increases the energy expenditure. Microtubules affinity regulated kinase 4 (Mark4) can regulate a variety of physiological processes. According to previous studies, we speculated that Mark4-autophagy-browning of white adipose tissue had certain linkages. Here, we established two autophagy models through serum starvation and rapamycin treatment and detected that the overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…It is one of the most important target tissues for obesity treatment. The cause of obesity may also be due to the production and pathological secretion of adipokines in adipose tissue, and it plays a role in the development of obesity-related diseases [ 16 ]. Apelin is one of these adipokines.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the most important target tissues for obesity treatment. The cause of obesity may also be due to the production and pathological secretion of adipokines in adipose tissue, and it plays a role in the development of obesity-related diseases [ 16 ]. Apelin is one of these adipokines.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that NP-cGMP signalling can also activate mTORC1 through PKG, thereby inducing adipose browning 63 . Many recent studies have found that certain regulatory factors, including SNS, T3, and Mark4, can affect autophagy by regulating mTOR, ultimately regulating thermogenesis 64 - 66 .…”
Section: Major Advances In Thermogenesis Signalling Pathways In Batmentioning
confidence: 99%
“…White adipocyte browning reduces adverse effects of white adipose tissue and protects against obesity, which may be a novel therapeutic target for atherosclerosis (Lo & Sun, 2013). Yang and colleagues (2020) reported that overexpression of MARK4 significantly inhibits browning of white adipose tissue by decreasing the expression of thermogenesis genes UCP1, PGC1α, Prd16, and Cideα. Thus, these findings suggest that MARK4 may promote the development of atherosclerosis via inhibiting the browning of white adipose tissue.…”
Section: Roles Of Mark4 In the Pathogenesis Of Atherosclerosismentioning
confidence: 99%
“…The major biological function of MARK4 is to phosphorylate the microtubule‐associated proteins, thereby increasing the dynamics of microtubule and promoting cell division, cell shape alterations, cell cycle control, and cell polarity determination (Annadurai et al, 2017; Naz et al, 2013). However, increasing evidence reveals that MARK4 has a variety of potential biological functions, including affecting lipid metabolism, inflammation, insulin signaling, and glucose homeostasis, white adipocyte browning, and oxidative stress (Z. Liu et al, 2016; C. Sun et al, 2012; Tian et al, 2019; Yang et al, 2020). Moreover, the expression of MARK4 is significantly increased in human atherosclerotic lesions compared with adjacent areas (Clement et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation